Improving the Performance of Heterogeneous Hadoop Clusters Using the Map Reduce Big Data Algorithm - Mr. Shivanshu Gautam, Mr. Sachin Jain, Ms. Amita Kashyap, Mr. Sheetal Kr. Dixit (International Journal of Advanced Science and Technology, 2019)
This article focuses on improving the performance of heterogeneous clusters in Hadoop after a series of steps that improve data I / O, improve the routing algorithm for heterogeneous clusters, and then improve query processing performance in such a way that they can be easily connected to the right part of execution in the shortest possible time without increasing costs at the computer level. The proposed work follows a series of steps to process these scenarios, which are described herewith.